2018
DOI: 10.1101/433029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous retroviruses transcriptional modulation after severe infection, trauma and burn

Abstract: 29 30 number of words: 5504 31 number of figures: 10 32 33 Keywords 34 Endogenous retroviruses -severe inflammatory injuries -septic shock -burn -trauma -transcriptome 35 -host response. 36 37 2 Abstract 38Although human endogenous retroviruses (HERVs) expression is a growing subject of interest, 39 no study focused before on specific endogenous retroviruses loci activation in severely injured 40 patients. Yet, HERV reactivation is observed in immunity compromised settings like some 41 cancers and auto-immu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The LTRC/D of MER41 is a member of the PRIMA41 elements that have been identified as enhancers for adjacent IFN-induced genes and have been shown to be involved in the regulation of essential immune functions [21]. Overall, differential expression analysis between HV and septic shock patients confirmed that septic shock is associated with an early modulation of thousands of HERV/ MaLR loci, which is in agreement with (1) in vitro LTR retrotransposons being tightly regulated to endotoxininduced stress [13] and (2) in vivo preliminary observations in critically ill patients [12].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The LTRC/D of MER41 is a member of the PRIMA41 elements that have been identified as enhancers for adjacent IFN-induced genes and have been shown to be involved in the regulation of essential immune functions [21]. Overall, differential expression analysis between HV and septic shock patients confirmed that septic shock is associated with an early modulation of thousands of HERV/ MaLR loci, which is in agreement with (1) in vitro LTR retrotransposons being tightly regulated to endotoxininduced stress [13] and (2) in vivo preliminary observations in critically ill patients [12].…”
Section: Discussionsupporting
confidence: 67%
“…Long terminal repeat (LTR) retrotransposons, which represent 8.3% of the human genome [11] were recently hypothesized to be relevant in the pathophysiology of sepsis [12,13]. These retrovirus-like sequences consist of approximately 200,000 human endogenous retroviruses (HERVs) and 240,000 mammalian apparent long terminal repeat retrotransposons (MaLR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three gene expression datasets analyzed in this study were downloaded from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ) and used to identify DEGs. GSE95233 [ 7 ], GSE57065 [ 8 ], and GSE28750 [ 9 ] were taken as representative datasets of patients with sepsis. For each dataset, data from day 1 of sample collection were used to analyze the gene expression based on the GPL570 platform (HG-U133_Plus_2).…”
Section: Methodsmentioning
confidence: 99%
“…GSE95233 [47] Whole blood 22 51 Affymetrix Human Genome U133 Plus 2.0 Array GSE57065 [48] Whole blood 25 28 Affymetrix Human Genome U133 Plus 2.0 Array GSE28750 [49] Whole blood 20 10 Affymetrix Human Genome U133 Plus 2.0 Array Series GSE65682 was analyzed using the Affymetrix HG-U129 platform, including 42 healthy samples and 760 patients admitted to the ICU with sepsis. 522 patients with sepsis among them were picked up for futher analysis.…”
Section: Materials and Methods 1 Gene Expression Datasets And Data Pmentioning
confidence: 99%